2017
DOI: 10.1128/jvi.01844-16
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanting a Simian Immunodeficiency Virus Vaccine with Toll-Like Receptor Ligands Encapsulated in Nanoparticles Induces Persistent Antibody Responses and Enhanced Protection in TRIM5α Restrictive Macaques

Abstract: Our previous work has shown that antigens adjuvanted with ligands specific for Toll-like receptor 4 (TLR4) and TLR7/8 encapsulated in poly(lactic-co-glycolic) acid (PLGA)-based nanoparticles (NPs) induce robust and durable immune responses in mice and macaques. We investigated the efficacy of these NP adjuvants in inducing protective immunity against simian immunodeficiency virus (SIV). Rhesus macaques (RMs) were immunized with NPs containing TLR4 and TLR7/8 agonists mixed with soluble recombinant SIVmac239-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 68 publications
6
89
2
Order By: Relevance
“…The exclusive presence of the PEG hydrophilic moieties in R848-NPb batches resulted in lower affinity of the drug to the polymer matrix leading therefore to lower encapsulation rates. In the literature, several studies relate the encapsulation of R848 or analogues in polymer nanoparticles either alone or co-encapsulated with antigens or adjuvants (Cruz et al, 2012;Ilyinskii et al, 2014;Kasturi et al, 2017Kasturi et al, , 2011Seth et al, 2017;Tacken et al, 2011;Tel et al, 2013). When encapsulation rates are given by the authors, the values are ranging from 1.2 to 6.4 μg/mg of NP.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusive presence of the PEG hydrophilic moieties in R848-NPb batches resulted in lower affinity of the drug to the polymer matrix leading therefore to lower encapsulation rates. In the literature, several studies relate the encapsulation of R848 or analogues in polymer nanoparticles either alone or co-encapsulated with antigens or adjuvants (Cruz et al, 2012;Ilyinskii et al, 2014;Kasturi et al, 2017Kasturi et al, , 2011Seth et al, 2017;Tacken et al, 2011;Tel et al, 2013). When encapsulation rates are given by the authors, the values are ranging from 1.2 to 6.4 μg/mg of NP.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kasturi et al reported enhanced protection of non-human primates against up to 12 low-dose intravaginal challenges with SIVsmE660. Interestingly, these results were achieved using PLGA-based NPs loading TLR 4/7/8 ligands as adjuvants, in a physical mixture either with the soluble immunogens Env and Gag or displayed in virus-like particles [185]. …”
Section: The Potential Of Nanotechnology For Vaccinationmentioning
confidence: 99%
“…Kasturi and Pulendran (30) investigated nanoparticles that encapsulated TLR4 and TLR 7/8 agonists and combined with SIV Env and Gag expressed as soluble proteins or VLPs. The nanoparticle-TLR formulation, in comparison to alum adjuvant, significantly enhanced the magnitude and persistence of antigen-specific antibody responses.…”
Section: Recent Preclinical Investigations With Hiv Vaccine-adjuvantmentioning
confidence: 99%